PERAN ELECTRONIC WORD OF MOUTH DALAM MEMBANGUN CITRA DESTINASI GUNA MEMPENGARUHI KEPUTUSAN BERKUNJUNG WISATAWAN KE SUATU DESTINASI PARIWISATA - Maftukhah Gustiani (Universitas Trunojoyo Madura, 2018)
ABSTRACTThis study aims to determine the role of electronic word of mouth in building a destination image to influence tourist decisions to a tourism destination. This research is a research. This research method is qualitative descriptive. Data collection methods used are through literature studies from several journals. The results of this study indicate that the better the electronic word of mouth, the more tourists will decide to visit a tourist destination. Electronic word of mouth communication is very influential on consumers who are interested in the advice of people who already have experience with tourist destinations which then create a brand image of a destination and decide to visit because of curiosity over the reviews he saw through social media. The better the electronic word of mouth, the better the image of a tourist destination. In other words, the impression of tourists on tourist destinations can arise after viewing posts or reading comments on social media accounts about tourist destinations.